Pengaruh Pertumbuhan Ekonomi Melalui Wisata Kuliner di Kambang Iwak Kota Palembang - Amalia, Zahara; Rahmawati, Vina; Vina Septiana, Nilam; Amalia, Lola; Panorama, Maya (Jurnal Etnik: Ekonomi-Teknik, 2022)
The purpose of this study was to determine the effect of economic growth through culinary tourism in Kambang Iwak, Palembang city. The obstacle faced by the kambang iwak traders, when the rainy season arrives, the plastic chairs that traders provide for wet buyers and even awards from the government if the Kambang Iwak traders belong to the creative economy class for Indonesian culinary tourism, especially the city of Palembang, there are no awards in the form of additional capital, certificates or placards about the best taste or the most crowded shops visited by people, so that Kambang Iwak traders can be even more creative in marketing their wares which is a culinary icon of the creative economy, especially the city of Palembang. This study uses a descriptive research approach using a qualitative approach. Results in. In this research, Culinary is one of the pillars of the creative economy. Culinary in Indonesia has great potential in Indonesia to continue to grow. The creative economy in Indonesia, especially in the Palembang area, is snacks in Kambang Iwak. Snacks are in demand by all walks of life, both children, teenagers, adults to the elderly, even traders in Kambang Iwak are well known outside of Palembang. Culinary has an important role to increase economic growth. Culinary is one of the creative economies. Creative economy in the form of culinary is the creativity of human resources as the main asset to create economic added value.